Effect of variation of operational regimes in building environment on results of its energy and exergy assessments = Wpływ zmienności funkcjonowania układów ogrzewania budynków na wyniki analizy egzergetycznej i energetycznej - Vološčuk, Volodimir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
For further development of the dynamic exergy analysis within built environment the work proposes to take into account stochastic nature of variations of operational regimes. Using the probability theory and statistics methods, the set of parameters considered as relevant for uncertainty conditions are presented.
Keywords: exergy-based methods; building environment; stochastic variations; reference environment; analiza egzergetyczna; ogrzewanie budynków; zmienna stochastyczna